Cost Avoidance Analysis of Medication Conversions on the Treatment of Gastroesophageal Reflux Disease in a Medication Therapy Management Call Center: A Budgetary Perspective. (June 2022) - Lai, Leanne; Alvarez, Goar; Aleu, Aisy; Apping, Caitlan
BACKGROUND: The burden of prescription drug prices affects patients and health system, creating a need for pharmacists to use their medication expertise to recommend the most cost-effective treatment for patients. OBJECTIVE: The study aimed to analyze the cost avoidance for medication conversions related to GERD from an integrated medication therapy management call center. METHODS: A quasi-experimental study was conducted at a call center during a 12-month intervention. Adult patients aged ≥18 years who received highercost PPIs were included. The pharmacists provided MTM services to patients telephonically to review all aspects of the patients' medication regimen as well as conversion recommendation to lower-cost PPIs. The cost avoidance analysis and sensitivity analysis were conducted. RESULTS: Of 40 eligible patients, 9 patients accepted the medication conversion, resulting in a 22.5% acceptance rate. The total cost avoidance from medication conversions was 19, 937.1 per year, which equated to 2, 215.2 per patient. The adjusted cost avoidance of medication conversion was estimated by assuming the patients who accepted the conversion continued taking the medication for 365 days and resulted in a total savings of 40, 370.7 per year, which equated to 4, 485.6 per patient. There were no significant association between the acceptance of medication conversions and patient's age(P = 0.15), gender(P = 0.73), and insurance status(P = 0.96). CONCLUSION: The study results showed that the call-center MTM with medicationconversion interventions successfully demonstrated an economically advantageous impact from a budgetary perspective. Further studies should explore methods to increase acceptance of MTM services and promote awareness of the profound effect on public health and well-being.